Kompensasi Terhadap Motivasi Kerja Karyawan Pada PT. Insolent Raya Di Surabaya - Abdul Aziz Sholeh; Indriana Kristiawati; Achmad Daengs GS; Rina Dewi; Retno Susanti; Ramansyah Hidayat (Universitas 45 Surabaya, 2024)
The purpose of this research is to analyze the influence of compensation on employee work motivation. The sample consists of employees of PT. Insolent Raya consisted of 32 respondents using the probability sampling method. The analysis used was validity testing, reliability testing, normality testing, and simple linear regression analysis. The results of this research show that the t test shows that there is a significant influence between the compensation variable (X) on the motivation variable (Y). The constant of 18.054 means that if the value of the compensation variable (X) is equal to 0, then the value of employee work motivation (Y) is 18.054. The compensation variable (X) has a positive regression coefficient. In other words, if the value of compensation (X) increases by 1 unit, then employee work motivation (Y) increases by the value of the regression coefficient or 0.535 times or 53.50%.